2019
DOI: 10.1177/0892705719874860
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on interfacial fracture toughness of 3-D printed ABS/CF-PLA composite under mode I, II, and mixed-mode loading

Abstract: Multimaterial structures made using fused deposition modeling (FDM) offer an attractive prospect for enhancing their mechanical properties and functionality. In this study, the interfacial fracture toughness of a unidirectional hybrid composite fabricated by FDM was studied through mechanical testing. The composite structure comprises acrylonitrile butadiene styrene and carbon fiber-reinforced polylactic acid. Since, de-adhesion or bond failure at the interface can occur under a combination of the different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The properties of these materials can be further increased by the addition of fibres and nanoparticles to achieve improved mechanical, thermal and chemical stability. [11][12][13][14][15][16][17][18] Recent studies have also shown that hybrid metalpolymer AM parts and dual polymer extrusion can further enhance the workability and properties of AM parts. 19,20 In addition to the inclusion of different phases, the properties of AM parts can be further improved by optimising the printing parameters adopted during the fabrication of the parts.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of these materials can be further increased by the addition of fibres and nanoparticles to achieve improved mechanical, thermal and chemical stability. [11][12][13][14][15][16][17][18] Recent studies have also shown that hybrid metalpolymer AM parts and dual polymer extrusion can further enhance the workability and properties of AM parts. 19,20 In addition to the inclusion of different phases, the properties of AM parts can be further improved by optimising the printing parameters adopted during the fabrication of the parts.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these filaments had a diameter of 1.75 mm (+0.5 mm). Their properties are listed in Table 1 [ 35 , 36 ]. These materials were purchased from the suppliers.…”
Section: Preliminary Experiments and Methodologymentioning
confidence: 99%
“…The properties such as high dimensional stability, high level of strength, and stiffness at an affordable cost make fiber-reinforced filaments an interesting material that opens new application fields in FDM printing. [18][19][20][21] In literature, continuous carbon fibers have been used as reinforcement materials of FDM printed ABS 22,23 and PLA. 24,25 The mechanical characterization of the printed composites indicated that the bending and tensile strengths were increased by up to 35% and 108%, respectively, in comparison with pure PLA while delamination together with matrix cracking were found as the dominant failure modes.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, continuous carbon fibers have been used as reinforcement materials of FDM printed ABS 22,23 and PLA. 24,25 The mechanical characterization of the printed composites indicated that the bending and tensile strengths were increased by up to 35% and 108%, respectively, in comparison with pure PLA while delamination together with matrix cracking were found as the dominant failure modes.…”
Section: Introductionmentioning
confidence: 99%